2020
DOI: 10.3390/ani10101916
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Intestinal Helminth Infections in Colic and Non-Colic Control Equine Patients

Abstract: All around the world, intestinal helminths constitute one of the most prevalent life-long occurring infections and re-infections affecting all horse age groups. A range of parasite species among strongyles, ascarids, and tapeworms is known to have the potential to cause colic in horses. However, there is a lack of current scientific evidence on the actual relevance of helminth infection levels in the context of colic in horses kept during prevailing epidemiological conditions. Thus, a prospective case-control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…The cut-off values for the rSvSXP-ELISA applied in the present study were 25 and 30%, which is a more conservative approach decreasing the number of false positives but also increasing the number of false negatives. High S. vulgaris seroprevalences were also reported in other studies (91,101), but are unexpected in light of surveys employing direct pathogen detection methods (14,15). The high number of serologically positive horses compared to the four horses tested S. vulgaris positive by realtime PCR may partly be due to the fact that early stages in the prepatency of the infection can be detected only with the ELISA.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The cut-off values for the rSvSXP-ELISA applied in the present study were 25 and 30%, which is a more conservative approach decreasing the number of false positives but also increasing the number of false negatives. High S. vulgaris seroprevalences were also reported in other studies (91,101), but are unexpected in light of surveys employing direct pathogen detection methods (14,15). The high number of serologically positive horses compared to the four horses tested S. vulgaris positive by realtime PCR may partly be due to the fact that early stages in the prepatency of the infection can be detected only with the ELISA.…”
Section: Discussionmentioning
confidence: 56%
“…The DNA samples positive in the pan-nematode PCR were further analysed using an S. vulgaris specific real-time PCR targeting a partial ITS-2 region initially described by Nielsen et al (48) as modified by Gehlen et al (91). As positive control, plasmid DNA containing the ITS-2 amplicon from S. vulgaris in the vector pSC-B-amp/kan (Aglient Technologies, Waldbronn, Germany) was used.…”
Section: Strongylus Vulgaris-specific Real-time Pcrmentioning
confidence: 99%
“…Studies performed in Sweden after the introduction of restrictions on prescribing, revealed 61% prevalence at the farm level and 9.2% and 28% prevalence in individual horses 261,281 . In Germany, prevalence was 1.1% by PCR 277 and a further study in Denmark reported a prevalence of 9.2% 262 . IgG(T) antibodies to recombinant S. vulgaris antigen have been identified in 75.9%, 62.1% and 59.4% of horses from Denmark, Sweden and Kentucky, respectively 253,279,281 …”
Section: Resultsmentioning
confidence: 96%
“…However, when specific types of colic were compared, horses diagnosed with peritonitis showed significantly higher ELISA scores than matched controls, possibly secondary to S. vulgaris associated non‐strangulating infarction 261 . A second prospective case–control study with 620 horses showed 1.1% of horses were positive by RT‐PCR and 32.3% by ELISA, however, there was no association between serological status and colic 262 . A retrospective case‐series performed in Denmark following mandatory implementation of diagnostic led de‐worming revealed similar S. vulgaris antibody concentrations between cases and controls; however, horses with non‐strangulating intestinal infarctions were more likely to be seropositive (OR 5.33, 95% confidence interval [CI]: 1.03–27.76) 263 .…”
Section: Resultsmentioning
confidence: 96%
“…In this prospective case‐control study Heidrun Gehlen and colleagues in Germany, USA, Italy and the UK investigated the association between colic and intestinal helminth infection.…”
Section: Intestinal Helminth Infectionsmentioning
confidence: 99%